Cereal Residues - Not a Waste Until We Waste it: A Review - Shahane, Amit Anil; Singh Shivay, Yashbir (International Journal of Bio-resource and Stress Management, 2023)
Residue generated along with economic plant part in cereal crops is voluminous. Management and effective utilization of residue for productive purpose is of prime importance in all major cereal growing area. In India about 416.5 mt of crop residue is generated from five major cereals (rice, wheat, maize, sorghum and pearl millet) in the year 2011-12. The management of residue is a major challenge in intensive cereal-based cropping systems where two or more cereals are grown in a single year. This is mainly due to low turn-around period and less preference as animal feed. The burden of managing bulky residue leads to adoption of easy but ecologically harmful ways like on-farm burning. On the other hand, the potential of cereal residue to contribute plant nutrient and carbon content along with various economic useful purposes need to be taken into account while managing it. In present review, we have discussed the residue potential, options for residue management with their pros and cons and research findings and research needs for effective utilization of residue under the following heads: 1) Potential of residue generation in India; 2) Options for utilization of generated residue; 3) Criteria for evaluation of residue management option; 4) Factor influencing selection of management option; 5) Residue management in reference to dry land agriculture; 6) Research, development and policy needs in residue management and 7) Model plan for residue management in Indian condition. In nutshell, our review emphasise management and efficient utilization of cereal residue, which leads to win-win situation for both environment and farmers.